The Effect of Financial Inclusion on Financial Sustainability and the Moderating Effect of Resource Dependence and Regulatory Quality in Iraq - Amin, Dr. Halkawt Ismail Mohammed Amin Mohammed; Arhinful, Dr. Richard Arhinful (Sulaimani Journal for Humanities, 2025)
Financial inclusion facilitates access to financial services for individuals and enterprises, promoting economic participation, alleviating poverty, and fostering growth. Enhancing financial stability and fostering long-term growth are paramount in Iraq. Prior studies have explored the effect of financial inclusion on financial sustainability from a cross-country perspective; however, this topic has received little attention in a single country like Iraq. Additionally, the moderating effects of resource dependence and regulatory quality on the relationship have been underexamined in the literature. This study employs institutional theory to explore the effect of financial inclusion on financial sustainability, examining how this relationship is moderated by resource dependence and regulatory quality. The research utilized 19 years of time series data, spanning from 2005 to 2023, obtained from the World Development Indicators (WDI) and the Federal Reserve Economic Data (FRED). The data were analysed using the Autoregressive Distributed Lag (ARDL) and Vector Error Correction Model (VECM) models, as the datasets were stationary and exhibited a long-run relationship. It was found that financial inclusion has both short-term and long-term significant and positive effects on financial sustainability. Moreover, the study found that the moderating effects of resource dependence and regulatory frameworks on financial inclusion exhibited both short-term and long-term positive and significant effects on financial sustainability. The government should implement measures that facilitate access to affordable financial services, strengthen regulations, promote digital banking, and enhance financial literacy to achieve equitable and sustainable growth.
Keywords: Financial inclusion; financial sustainability; Resource dependence; regulatory quality; Inflation